2015
DOI: 10.5539/res.v7n11p103
|View full text |Cite
|
Sign up to set email alerts
|

Future Pedagogues’ Attitudes and Knowledge about Inclusive Education in Spain: an exploratory study

Abstract: This article analyses the attitudes and knowledge about inclusive education among students reading Pedagogy at the University of Valencia and how these are influenced by participants' age, gender, and which academic programme or year of study they are in. This research comprises a sample of 182 students from the degree's four year groups, which guarantee a representativeness of 95%. The principal results indicate that attitudes towards inclusive education among students reading Pedagogy are highly positive. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(61 reference statements)
0
2
0
1
Order By: Relevance
“…The worldwide recognition of the need for diversity learning in mainstream university teacher education departments combats exclusion and marginalisation in the learning and teaching process and promotes diversity and inclusion. Without adequate teacher preparation for inclusive learning (and inclusive reading), recently graduated teachers encounter challenges in their attempts to facilitate diverse learning in classrooms (López-Torrijo & Mengual-Andrés, 2015;Subban & Mahlo, 2017).…”
Section: Teaching Inclusive Reading In South African Mainstream Schoolsmentioning
confidence: 99%
“…The worldwide recognition of the need for diversity learning in mainstream university teacher education departments combats exclusion and marginalisation in the learning and teaching process and promotes diversity and inclusion. Without adequate teacher preparation for inclusive learning (and inclusive reading), recently graduated teachers encounter challenges in their attempts to facilitate diverse learning in classrooms (López-Torrijo & Mengual-Andrés, 2015;Subban & Mahlo, 2017).…”
Section: Teaching Inclusive Reading In South African Mainstream Schoolsmentioning
confidence: 99%
“…Most studies focus on reading instruction and the acquisition of decoding skills. Teachers seem to be inadequately prepared to teach comprehension as various studies in South African school contexts have shown (Pretorius & Klapwijk, 2016;Klapwijk, 2011;Mengual-Andrés et al, 2015;Subban & Mahlo, 2017). All teachers should have adequate skills to teach literacy comprehension and language acquisition regardless of the subject they teach in the classroom (Lu et al, 2022).…”
Section: Teacher Challenges In Engaging With Comprehension Instructionmentioning
confidence: 99%
“…According to the teachers’ gender, the studies analysed show significant differences between male and female teachers in their implementation of inclusive practices with students with disabilities. Specifically, there are studies (Alghazo & Naggar, 2004; Mengual, López, & Viana, 2015; Parasuram, 2006; Polo & Aparicio, 2018) which show that male teachers implement more inclusive practices. However, studies like those by Boyle, Topping, and Jindal-Snape (2013) and Opdal, Wormnaes, and Habayeb (2001) conclude that female teachers promote better practices compared to their male counterparts.…”
Section: Teaching Factors In the Development Of Inclusive Practicesmentioning
confidence: 99%
“…Según el género de los docentes, las investigaciones analizadas muestran diferencias significativas entre el profesorado en cuanto al desarrollo de prácticas inclusivas con alumnos con discapacidad. De este modo, se constatan estudios (Alghazo & Naggar, 2004; Mengual, López, & Viana, 2015; Parasuram, 2006; Polo & Aparicio, 2018) en los que se revelan condiciones más positivas entre los profesores para el desarrollo de prácticas inclusivas. En contraposición, estudios como los desarrollados por Boyle, Topping, y Jindal-Snape (2013) y Opdal, Wormnaes, y Habayeb (2001) concluyen cómo las profesoras promueven mejores prácticas en comparación con los profesores varones.…”
Section: Factores Docentes En El Desarrollo De Prácticas Inclusivasunclassified